Teachers’ perceptions of students with special education needs in Two Western Districts of Bhutan - Womling, Tshering; Dhendup, Sonam (International Journal of Humanities and Education Development (IJHED), 2020)
The present study examined Bhutanese teachers’ general perceptions, challenges towards special educational needs (SEN) students, and professional development (PD) and training attended by teachers with their levels of stress. A total of 53 teachers of Two SEN Schools in western Bhutan participated in this study. The data were collected using the online survey. The findings of this study suggest that although, 55% of teachers felt that teaching students with or without disabilities together is a good thing, however, the lack of professional development and further training can thus be a contributing factor why teachers feel stress while teaching students with SEN in these two identified schools. The findings also indicated that teachers learnt skills in SEN mostly through personal initiatives such a doing further research and reading. Similarly, the results of the study showed that the female teachers were said to have experienced more stress compared to their male counterparts. Further, the study also revealed that some of the challenges identified by teachers while teaching students with SEN were the lack of teacher collaboration within the school, lack of resources, overcrowded classrooms and the lack of professional development and training. Alternatively, the results of predictive analysis tended to show a strong negative relationship between the PD and the teacher stress. Further, the correlation and the prediction analyses further revealed that an estimated of 52% variability of stress can be predicted by the PD/trainings attended by the teachers.